Assessment of Elemental Pollution in Marine Sediment from Talang-Satang and Bako National Park of Sarawak, Malaysia (Special Issue> Malaysian Nuclear Agency) - Md Suhaimi, Elias; Mohd Suhaimi, Hamzah; Ab Khalik, Wood; Azian, Hashim; Shamsiah, Ab Rahman; Wee, Boon Siong; Nazaratul Ashifa, Abdullah Salim (放射化分析研究会, 2013)
The assessments ofelemental polluti oinn sediment collected from national park ofSarawak were done based on their distribution pattern ,geoaccumulation index and enrichment factor ,The enrichment factor s(EF )were determined by the elemental rationing method, whilst the geoaccumulati oinndex (Ig .by. )comparing of current concentration to background concentration of metals, The elements were analyzed by using Instmmenta1 Neutron Activatio nAnalysis (INAA) .The results of enrichment facto rshow tha tTalang-Satang and Bako National Park have significant contaminated by toxic elements such as As, Cr, Sb, Ti and U. Base on the classification system proposed for sediment qualit ywith referring to Ig. ,the sediment quali tyof the Talang-Satang and Bako National Park for Arsenic (As) contamination can be categorized as moderate to extremely contaminated. Contamination of element such as Cr, Sb and Ti can be categorized as uncontaminated to moderate contaminated, and U can be categorized as uncontaminated to moderate and strong contaminated, The average concentration of As in sediment of Bako shown surpassed sediment qualit yguidelin eCprobable effect concentration - PEC) value, whilst Cr concentration in sediment of Talang-Satang shown above midpoint effect concentration (MEC) .This indicatin gt,he sediment ofBako and Talang-Satang could have a potentia lfor producing chronic effect to the marine biot aor benthi ocrganism.